The refugee crisis - Harris, Duchess; Herschbach, Elisabeth (Special reports (Essential Library (Firm)), 2019)
Examines the current refugee crisis around the globe, discussing the situation in various countries, the reasons refugees risk their lives on dangerous journeys, their right to asylum, and responses to the crisis. Includes sidebars, a glossary, resources for further information, maps, and color photographs.